Ganglioside Metabolism and Parkinson's Disease - Forsayeth, John; Hadaczek, Piotr (Frontiers in Neuroscience, 2018)
Here we advance the hypothesis that Parkinson’s disease (PD) is fundamentally a failure of trophic support for specific classes of neurons, primarily catecholaminergic. Evidence from our laboratory provides a framework into which a broad array of findings from many quarters can be integrated into a general theory that offers testable hypotheses to new and established investigators. Mice deficient in the ability to synthesize series-a gangliosides, specifically GM1 ganglioside, develop parkinsonism. We found that this seems to be due to a failure in signaling efficiency by the important catecholaminergic growth factor, GDNF. Interestingly, these mice accumulate alpha-synuclein in nigral neurons. Striatal over-expression of GDNF eliminates these aggregates and also restores normal motor function. These findings bring into question common beliefs about alpha-synuclein pathology and may help us to reinterpret other experimental findings in a new light. The purpose of this article is to provoke new thinking about PD and hopefully encourage younger scientists to explore some of the ideas presented below.